2017
DOI: 10.1080/14767058.2017.1326901
|View full text |Cite
|
Sign up to set email alerts
|

Trends and characteristics of fetal and neonatal mortality due to congenital anomalies, Colombia 1999–2008

Abstract: Objective To describe fetal and neonatal mortality due to congenital anomalies in Colombia. Methods We analyzed all fetal and neonatal deaths due to a congenital anomaly registered with the Colombian vital statistics system during 1999–2008. Results The registry included 213,293 fetal deaths and 7,216,727 live births. Of the live births, 77,738 (1.08%) resulted in neonatal deaths. Congenital anomalies were responsible for 7321 fetal deaths (3.4% of all fetal deaths) and 15,040 neonatal deaths (19.3% of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
3
30
1
1
Order By: Relevance
“…A study analysed all foetal and neonatal deaths due to a congenital anomaly registered with the Colombian vital statistics system from 1999 to 2008 (Roncancio et al 2018(Roncancio et al :1749.…”
Section:  Infectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study analysed all foetal and neonatal deaths due to a congenital anomaly registered with the Colombian vital statistics system from 1999 to 2008 (Roncancio et al 2018(Roncancio et al :1749.…”
Section:  Infectionsmentioning
confidence: 99%
“…It reported that male sex was associated with slightly higher mortality due to congenital anomalies than female sex (Roncancio et al 2018(Roncancio et al :1749. In rural Tanzania, a study found that neonatal mortality was higher for male newborns than females; it suggested that this increased hazard for newborn males may also be due to the large proportions of neonatal deaths occurring in the first week of life, which is the time when gender differences in neonatal mortality are most pronounced (Selemani, Mwanyangala, Mrema, Shamte, Kajungu & Mkopi 2014:6).…”
Section:  Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Congenital heart disease is the leading cause of birth defect-related mortality, accounting for approximately 40% percent of deaths in children with birth defects in the United States and worldwide. [1][2][3][4] Prior studies have demonstrated decreasing mortality over time in CHD in the United States, likely due to marked advances in medical and surgical care. 5,6 The most comprehensive assessment in the United States to date was a population-based study evaluating CHD mortality from 1999 through 2006.…”
Section: Introductionmentioning
confidence: 99%